How rational is gambling? - Robin Maximilian Stetzka; Stefan Winter (Journal of Economic Surveys, 2021)
The typical gambler loses money but continues to gamble nonetheless. Why? Research from orthodox and behavioral economics, psychology, sociology, and medicine has offered a wide range of possible explanations. This paper reviews these explanations. The evidence is organized according to the degree of rationality assumed and/or found in the studies. This approach allows research from highly distinctive fields to be integrated within a unified framework. Gambling patterns are so highly dispersed that no satisfying one-fits-all explanation is possible. The findings suggest that the whole spectrum from rationality to highly destructive irrationality can be found within the gambler population.
Keywords: 330; bounded rationality; consumption benefits; gambling; gambling behaviour; irrationality; rationality